On the World Co2 Emission Equitable Transition Design and Its Implementation: Theory and Empirical Data - Bova, Demetrio Miloslavo (European Journal of Sustainable Development, 2021)
This paper designs the transition trajectory for Co2 emissions that considers the impact on inequality both across countries and generations and introduces elements for its implementation. The intercountry and intergenerational equities are discussed and found, for the first, in terms of equal cumulated per capita emissions, for the second, both in terms of temperature growth control and capacity to ensure an equal future yearly amount of emission per generation. These definitions allow enquiring which country is behaving fairly and, consequently, which system may be introduced to compensate. Once the emission trajectory is defined, its implementation and the deviances management can be structured through a quasi-decentralised dynamic cap and trade system. Theory and empirical data for the design and its management are provided.